Stephen Mason and Daniel Seng (Editors) (2021) Electronic Evidence and Electronic Signatures (5th ed.) University of London Press - Rilwan Funsho Mahmoud (Law, Technology and Humans)
Rilwan F. Mahmoud reviews Electronic Evidence and Electronic Signatures by Stephen Mason and Daniel Seng